The Indeterminacy of Trust. A Response to Möllering and Esposito’s Commentaries - Gil Eyal; Larry Au; Cristian Capotescu (Sociologica, 2024)
We reply to Esposito and Möllering by clarifying what we meant by the procedure of “critical reconstruction”. It is not an external critique, because we have carefully followed the logic of trust research. But it is also not easily reconcilable with trust research, as Möllering argues, because we show that by doing so one is led to certain aporias, conundrums, and contradictions that do not permit leaving the concept as we found it. We reject any attempt to found the concept of trust in a theoretical constant such as complexity or irreducible uncertainty, and emphasize the need for an ethnomethodological approach that limits itself to how the actors themselves draw the distinctions between trust and blind faith, trust and mistrust, etc. This commitment is all the more necessary now, when trust research has become part of the very phenomenon it studies.